Republic of Belarus : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Selected Issues paper analyzes the causes of the high inflation in Belarus. It estimates the contribution of two factors: (1) exchange rate pass-through and (2) administrative price increases. Residual inflation is used as a gauge for inflation caused directly by demand pressures and inflation expectations. It is found that the administrative price increases are a key driver of inflation, even ahead of demand pressures, which also explain a large share of inflation. Although exchange rate pass-through is found to be high and fast, particularly for unregulated prices, its contribution to inflation has been comparatively modest in recent years owing to the stability of the exchange rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet